Health-related quality of life in multiple sclerosis patients with bladder, bowel and sexual dysfunction. (June 2014) - Vitkova, Marianna; Rosenberger, Jaroslav; Krokavcova, Martina; Szilasiova, Jarmila; Gdovinova, Zuzana; Groothoff, Johan W.; van Dijk, Jitse P.
Abstract Purpose: Bladder, bowel and sexual dysfunction are often overlooked symptoms in patients with multiple sclerosis (MS) and can be associated with lower health-related quality of life (HRQoL). The aim is to explore the association of bladder, bowel and sexual dysfunction with HRQoL in MS patients stratified by disease duration (≤5 and >5 years) and controlled for clinical and sociodemographic variables. Methods: The study comprised 223 MS patients (mean age 38.9 ± 10.8 years, 67% female, mean EDSS 3.0 ± 1.5) who filled out the Short-Form-36 Health Survey, the Bladder Control Scale, the Bowel Control Scale and the Incapacity Status Scale. The relationships between the variables were analyzed with multiple linear regression using the SF36's Physical Component Summary (PCS) and Mental Component Summary (MCS) as dependent variables. Results: More severe bladder dysfunction was associated with lower PCS in both disease duration groups (β = −0.35, p ≤ 0.001 versus β = −0.43, p ≤ 0.001), whereas more severe sexual dysfunction was associated with lower MCS in the group with shorter disease duration (β = −0.23, p ≤ 0.05). Conclusion: Bladder and sexual dysfunction are associated with a poorer HRQoL in MS patients even if they have had MS for a relatively short time. Recognition and proper treatment is needed to prevent the development of more severe dysfunction; this may also lead to a better HRQoL. Implications for Rehabilitation Bladder and sexual dysfunction are associated with a poor health-related quality of life in MS patients. Sexual dysfunction may explain mental health issues among individuals with a short disease duration. Recognition and treatment may prevent the development of more severe sexual and bladder dysfunction and increase physical health-related quality of life.